Autogeneic RNA-electroporated CD40-ligand activated B-cells from hepatocellular carcinoma patients induce CD8+ T-cell responses ex vivo - Shen, S.; Xu, Z.; Qian, X.; Ding, Y.; Yu, L.; Liu, B. (Experimental Oncology, 2007)
Since dendritic cells (DCs) constitute only 0.1–0.5% of human peripheral blood mononuclear cells (PBMCs), and generation of DCs from monocytes or stem cells is difficult and expensive, we choose B-lymphocytes as an alternative, cost-effective source of antigen presenting cells (APC). Aim: To induce specific CTLs response ex vivo by CD40L activated B-cells (CD40-B) transfected with hepatocellular carcinoma (HCC) total RNA. Methods: To induce CD40-B PBMCs of patients with HCC were isolated by Ficoll technique and cultured in RMPI 1640 supplemented with 10% fetal calf serum (FCS), sCD40L (2 µg/ml), recombinant human interleukin-4 (IL-4) (4 ng/ml). The expression of CD80 and CD86 was evaluated by flow cytometry. The level of interleukin-12 (IL-12) produced by cultured B-lymphocytes was measured using enzyme-linked immunosorbent assay (ELISA). HCC patient’s T-lymphocytes were obtained from PBMCs cultured in RMPI 1640 supplemented with 10% FCS, 2 ng/mL IL-4 and 10 ng/ml IL-7. CD40-B transfected with tumor total RNA isolated from HCC cells were used to induce specific CTL proliferation. The level of IFN-g was measured using ELISA and the expression of CD8 was determined by FCAS. Specific cytotoxicity was measured using MTT method. Results: The results show that the activated B-lymphocytes were easily expandable and formed large clones, and a high expression of CD80/CD86 and a high IL-12 secretion by CD40-B was registered. CD40-B transfected with tumor total RNA can induce CTLs to express CD8 and generate IFN-g at high levels. Compared to the control group, the specific cytotoxicity of CTLs was up-regulated. Conclusion: These findings demonstrate that CD40-B-cells electroporated with total RNA derived from carcinoma cells can be used as alternative APC for the induction of antigen-specific CD8+ T-cell responses, which might be used in HCC immunotherapy. Поскольку дендритные клетки (ДК) составляют только 0,1–0,5% мононуклеаров периферической крови (МПК) человека, и
получение ДК из моноцитов и стволовых кроветворных клеток является трудоемкой и дорогостоящей процедурой, выбраны
В-лимфоциты в качестве альтернативного источника антигенпрезентирующих клеток (АПК). Цель: изучить возможность
активированных CD40-лигандом В-лимфоцитов (CD40-B), трансфецированных суммарной РНК, выделенной из клеток
гепатоцеллюлярной карциномы, индуцировать специфический ответ цитотоксических Т-лимфоцитов ex vivo Методы: МПК
пациентов с гепатоцеллюлярной карциномой изолировали на градиенте фиколла и культивировали в среде RMPI 1640 с
10% эмбриональной сыворотки телят (ЭСТ), sCD40 (2 мкг/мл) и рекомбинантным человеческим интерлейкином-4 (ИЛ-4,
4 нг/мл). Экспрессию СD80 и CD86 оценивали на проточном цитофлюориметре. Концентрацию интерлейкина-12, продуцируемого
культивируемыми В-лимфоцитами, оценивали с помощью иммуноферментного анализа (ИФА). Т-лимфоциты
получали из МПК пациентов с гепатоцеллюлярной карциномой и культивировали в среде RMPI 1640 с 10% ЭСТ, 2 нг/мл
ИЛ-4 и 10 нг/мл ИЛ-7 и культивированы совместно с CD40- клетками, трансфецированными опухолевой РНК, для
индукции пролиферации специфических цитотоксических Т-лимфоцитов. Уровень интерферона- (ИНФ-γ) определяли с
помощью ИФА, а экспрессию CD8 на проточном цитофлуориметре. Специфическую цитотоксичность оценивали в МТТ
тесте. Результаты: показано, что активированные in В-лимфоциты формируют большие колонии, на поверхности
клеток отмечается высокая экспрессия антигенов CD80/CD86, и ими в повышенных количествах секретируется ИЛ-12.
CD40-B-лимфоциты, трансфецированные опухолевой РНК, могут активировать CD + цитотоксические лимфоциты, которые
продуцируют ИНФ-γ. Выводы: CD40-B-клетки, трансфецированные суммарной РНК, выделенной из опухолевых
клеток больных с гепатоцеллюлярной карциномой, — это альтернативные АПК для индукции антигенспецифического CD +
T-клеточного ответа, что может быть использовано для иммунотерапии пациентов с гепатоцеллюлярной карциномой.